Building and Sustaining Scholarly Communities in Health Professions Education: Lessons from U.S. Academies - Anthony R. Artino; Jr.; Zareen Zaidi; Farida Izzi; Shazia Samanani; Navin Sampathkumar; Ahdeah Pajoohesh-Ganji (Perspectives on Medical Education, 2026)
Introduction: Academic health centers have invested in academies to promote health professions education scholarship, yet many struggle to sustain vibrant scholarly communities. We aimed to identify practices that support their development and long-term sustainability. Methods: Using a constructivist approach, we conducted a qualitative interview study in 2025 with leaders from all four geographic regions of the U.S. Inclusion criteria required that participants direct an academy or analogous institutional structure intended to promote educational scholarship, and that they could speak to building and sustaining this community in their local context. The Communities of Practice (CoP) framework informed interview guide development and data interpretation. Results: Twenty-one academy leaders described five interrelated forms of leadership work that shaped sustainable scholarly communities: (1) building foundations that legitimize educational scholarship by securing institutional investment, leadership buy-in, and succession planning; (2) cultivating scholarly sanctuary to counter isolation through psychologically safe, inclusive communities; (3) making scholarship feasible under constraints by creating low-barrier entry points, translating value to leaders, and addressing barriers; (4) tending growth through layered, incremental development, including cohort programs, consultation, mentoring, grants, and flexible participation; and (5) making educational scholarship visible and valued through recognition, dissemination, and outcome tracking. Discussion: Viewed through the CoP framework, the themes illuminate how leaders cultivated a shared domain of legitimate educational scholarship, a community of relational support, and a practice of tools, routines, and developmental infrastructure. The themes also reveal that sustainable communities of practice do not emerge from any single academy model, but from context-sensitive alignment of structure, culture, and incentives.